2016
DOI: 10.1039/c6ta05409a
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a hierarchical hollow hematite nanostructure for lithium storage

Abstract: A new hierarchical hollow α-Fe2O3 nanostructure that has a nanosphere morphology of approximately 250 nm in diameter integrated with ensembles of 15 nm diameter nanotubes is designed and engineered. As an anode material for Li-ion batteries, the HHFN exhibits significantly improved Li storage capability, good cycling stability, as well as high-rate performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Figure 5a shows the first five CV curves of the Fe 2 O 3 @3DG-150 at a scan rate of 0.1 mV s −1 in the voltage window of 0.01-3.0 V. In the initial cathodic process, the presence of the peak at 1.55 V indicates that the irreversible conversion between Li + and Fe 2 O 3 leads to the formation of a solid electrolyte-interphase (SEI) layer [39]. Another apparent characteristic peak at 0.65 V was attributed to the formation of irreversible Li x Fe 2 O 3 (Fe 2 O 3 + Li + + e − → Li x Fe 2 O 3 ) [40].…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…Figure 5a shows the first five CV curves of the Fe 2 O 3 @3DG-150 at a scan rate of 0.1 mV s −1 in the voltage window of 0.01-3.0 V. In the initial cathodic process, the presence of the peak at 1.55 V indicates that the irreversible conversion between Li + and Fe 2 O 3 leads to the formation of a solid electrolyte-interphase (SEI) layer [39]. Another apparent characteristic peak at 0.65 V was attributed to the formation of irreversible Li x Fe 2 O 3 (Fe 2 O 3 + Li + + e − → Li x Fe 2 O 3 ) [40].…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…For instance, Mao et al reported that constructing hierarchical α-Fe 2 O 3 nanospheres with hollow interiors could not only efficiently enhance electroconductivity but also tailor the properties of Li + ion storage, achieving satisfactory long-term cycling stability of retaining a reversible capacity of 965 mA h g −1 beyond 200 cycles. 27 Such a high capacity for Li-ion storage was far superior to that of the commercial graphite material with the theoretical value of 372 mA h g −1 . 28 As shown in Fig.…”
Section: Introductionmentioning
confidence: 96%
“…[5] To find better alternatives to graphite, researchers have investigated many new anode materials with higher capacity, including metal, metal oxides, metal sulfides, metal nitrides. [6][7][8][9][10][11] Among all kinds of anode materials, transition metal oxides and hydroxides, especially cobalt based compounds, due to the high lithium storage capacity, as well as natural abundance and environmental DOI: 10.1002/crat.202100133 friendliness have attracted much attention as promising alternative anode materials. [12,13] However, there are some problems in metal oxides and hydroxides as anodes for LIBs.…”
Section: Introductionmentioning
confidence: 99%